Maintaining Transmission: DirecTV's Work-at-home Technical Support, Virtual Surveillance, and the Gendered Domestication of Distributive Labor. (September 2021) - Patterson, Eleanor
This article draws upon interviews with work-at-home (WAH) agents who did technical support for DirecTV between 2009 and 2016. Satellite television technical support workers comprise an important node in maintaining the flow of television content as it is distributed by corporations, like DirecTV, through complex and often fragile technological conditions. Using interviews, trade press, and online employee forums, I outline the history of DirecTV's WAH call center work and employment conditions, and its dissolution after the merger with AT&T. This research intervenes to demonstrate the ways in which WAH television technical support work is an ambivalent form of distributive media labor, at once feminine and immaterial, while also creative and essential for television distribution. This article also demonstrates how technical support work is influenced by current precarious and digitally converged working conditions, surveillance tactics, and media conglomerate mergers and structures.